2009
DOI: 10.1210/jc.2009-0179
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Fibroblast Growth Factor Receptor 1 Signaling as a Cause of Normosmic Idiopathic Hypogonadotropic Hypogonadism

Abstract: Loss-of-function mutations in FGFR1 underlie 7% of nIHH with different degrees of impairment in vitro. These mutations act in concert with other gene defects in several cases, consistent with oligogenicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
113
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(125 citation statements)
references
References 46 publications
8
113
0
4
Order By: Relevance
“…4). FGFR1 R250 is involved in binding FGF8 (32), and was independently associated with another case of GnRH deficiency (33). Because FGFR1 requires HS 6-O-sulfation for interaction with FGF8 (32), the HS6ST1 R296W and FGFR1 R250Q mutations may synergize to compromise FGF signaling, consistent with prior reports of digenicity (17,24,34,35).…”
Section: Ihh Associated With Hs6st1 Mutations Displays Clinical Hetersupporting
confidence: 78%
“…4). FGFR1 R250 is involved in binding FGF8 (32), and was independently associated with another case of GnRH deficiency (33). Because FGFR1 requires HS 6-O-sulfation for interaction with FGF8 (32), the HS6ST1 R296W and FGFR1 R250Q mutations may synergize to compromise FGF signaling, consistent with prior reports of digenicity (17,24,34,35).…”
Section: Ihh Associated With Hs6st1 Mutations Displays Clinical Hetersupporting
confidence: 78%
“…Neither FGF was able to induce luciferase activity in cells transfected with an expression vector lacking an Fgfr cDNA (empty vector), whereas, as expected, FGF8, but not FGF10, induced luciferase activity significantly above background levels in cells transfected with a wild-type FGFR1c expression vector. FGFR1c was also activated by FGF2 to the same extent seen by Raivio et al (2009) (data not shown). These control conditions confirmed that there is no endogenous FGFR expression in L6 cells (Olwin and Hauschka 1989;Roghani et al 1996) and that there is endogenous FGF expression and/or perdurant FGF from the serum used to culture the L6 cells.…”
Section: Fgf10 Activates Fgfr3b P244r and Fgfr3c P244r But Not Their mentioning
confidence: 52%
“…Both the wild-type and mutated cDNAs were transferred into the pcDNA1 expression vector used by Chellaiah et al (1994) to express other Fgfr3 constructs. A human FGFR1c expression vector (Raivio et al 2009) was used as a control. The FGFresponsive OCFRE-luc vector was described previously (Newberry et al 1996).…”
Section: Transient Transfection Of L6 Myoblasts To Assay Fgfr Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Part of this phenomenon can be explained by the interaction of mutations in two or more genes/proteins (oligogenicity) as has been reported in several studies (19,25,28). Further, some patients with reversible CHH harbor mutations in genes implicated in CHH, (29) including cases of oligogenicity (30). Such reversal cases highlight the importance of environmental (i.e.…”
Section: Pathophysiology and Genetics Of Chhmentioning
confidence: 86%